Far Away but Similar: Peaceful Coexistence Models in Indonesia and Syria - Kostanian, Ararat (Universitas Islam Internasional Indonesia (UIII), 2024)
Successful social coexistence in countries with multiethnic and multireligious populations is rare. Scholars have used different approaches to find the theory that explains the key elements communities perform in reaching an environment of peaceful coexistence. In this regard, the previous theories give us a partial understanding of the successful peaceful existence amid rising conservatism in global scale. Drawing from Robert Putnam’s social capital theory, this article argues that peaceful coexistence in Syria and Indonesia has been successful due to several factors: the historical, trust and reciprocity, social network and the nationalist sentiment. The empirical research was done by analyzing academic, analytic, and historical data, conducting interviews, and fieldwork with community members in Syria and Indonesia.